The Influence of Career Development, Compensation and Job Satisfaction on The Performance of Temporary Employees in Flood Prevention Institution in East Java - Sumarno, Sumarno; Suyono, Joko; Pratama, R. Dandy Jurindra; Salamin, Akhmad Lutfis; Suyono, Aldrin Arizona (Universitas Muhammadiyah Gresik, 2025)
his study aims to determine the partial and simultaneous influence of independent variables (careerdevelopment, compensation, and job satisfaction) on the dependent variable (temporary employees'performance) in Flood Prevention Institution in East Java and to determine the independent variable thathas a dominant influence on the dependent variable. The sampling technique used is probabilitysampling. The sample used in this study was 67 of the 197 temporary employees in Flood PreventionInstitution in East Java. The data analysis uses multiple linear regression and hypothesis testing using theSPSS test tool. The results prove that career development, compensation, and job satisfaction partiallyand simultaneously influence the performance of temporary employees. In addition, the compensationvariable has a dominant influence on the performance of temporary employees in Flood PreventionInstitution in East Java, with a partial influence of 46.6%.